Deklaratywna a rzeczywista popularność analizy technicznej - Kubińska, Elżbieta; Markiewicz, Łukasz; Czupryna, Marcin (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The study confirms the enormous popularity of technical analysis methodsamong investors. Technical analysis was evaluated as the most important toolfor supporting investment decisions. However, what investors declare is differentfrom what in fact they do. The attitude towards technical analysis declaredin the questionnaire was not correlated with the actual behavior in the game.The impact of technical analysis on the final value of the portfolio was examinedtoo and the results depend on the type of signal. Signals based on indicators had a positive impact on the final value of the portfolio while the signals based on theAlexander’s filters had a negative impact.